Beauty Premium through Cosmetic Surgery for Prisoners: Choice Experiment with Asymmetric Information - Phuchongpravech, Taksaorn; Chaiwat, Thanee (Thailand and The World Economy, 2021)
The concept of ‘beauty premium’ has been the subject of academic research for decades, but only a few studies have investigated the investment side of beauty. Meanwhile, the main concern of prisoners is to be given the opportunity to re-enter society. However, their low physical attractiveness has been claimed to be an obstacle that prevents them from entering the labour market. While a large literature reported the existence of beauty premium in the labour market worldwide, the current paper complements the existing literature by applying choice experiment (CE) with asymmetric information to investigate the impacts of cosmetic surgery on prisoners’ labour market returns: job opportunities and incomes. Eighteen male prisoners’ faces were simulated for cosmetic surgery and assigned as job candidates in a CE. The results show that, compared with the non-surgical group, respondents (employers) in the formal and informal sectors preferred cosmetic surgical groups with odds ratios or increase of utility of 4.05 and 2.54, respectively. The MWTP values show that employers are willing to pay an additional 3,500 baht to the surgical group. Using prisoners as subjects not only broadens existing literature by demonstrating the existence of economic returns to investment on beauty in this minority group, but it also presents additional ideas for further rehabilitation programme to help prisoners reintegrate themselves into society.